Association of physical workload and leisure time physical activity with incident mobility limitations: a follow-up study. Issue 8 (30th May 2014) - Mänty, M; Møller, A; Nilsson, C; Lund, R; Christensen, U; Avlund, K
Abstract : Objectives: To examine individual as well as joint associations of physical workload and leisure time physical activity with incident mobility limitations in initially well-functioning middle-aged workers. Methods: This study is based on 6-year follow-up data of the Danish Longitudinal Study on Work, Unemployment and Health. Physical workload was reported at baseline and categorised as light, moderate or heavy. Baseline leisure time physical activity level was categorised as sedentary or active following the current recommendations on physical activity. Incidence of mobility limitations in climbing stairs and running among initially well-functioning workers (n=3202 and n=2821, respectively) was assessed during follow-up. Results: Higher workload increased whereas active leisure time decreased the risk of developing mobility limitations. The incidence of limitations increased progressively with higher workload regardless of level of leisure time physical activity, although the risks tended to be higher among those with sedentary leisure time compared with their active counterparts. All in all, the risk for onset of mobility limitations was highest among those with heavy workload combined with sedentary leisure time and lowest among those with light workload combined with active leisure time. Conclusions: Although leisure time physical activity prevents development of mobility decline, high workload seems to accelerate the progression of mobility limitations among both those with active and sedentary leisure time. Therefore, efforts should be made to recommend people to engage in physical activity regardless of their physical workload.